Improving the classification accuracy using hybrid techniques - Mamdouh Abdel Alim Saad Mowafy; Walaa Mohamed Elaraby Mohamed Shallan (Review of Economics and Political Science (REPS), 2021)
Purpose Heart diseases have become one of the most causes of death among Egyptians. With 500 deaths per 100,000 occurring annually in Egypt, it has been noticed that medical data faces a high-dimensional problem that leads to a decrease in the classification accuracy of heart data. So the purpose of this study is to improve the classification accuracy of heart disease data for helping doctors efficiently diagnose heart disease by using a hybrid classification technique. Design/methodology/approach This paper used a new approach based on the integration between dimensionality reduction techniques as multiple correspondence analysis (MCA) and principal component analysis (PCA) with fuzzy c means (FCM) then with both of multilayer perceptron (MLP) and radial basis function networks (RBFN) which separate patients into different categories based on their diagnosis results in this paper, a comparative study of the performance performed including six structures such as MLP, RBFN, MLP via FCM-MCA, MLP via FCM-PCA, RBFN via FCM-MCA and RBFN via FCM-PCA to reach to the best classifier. Findings The results show that the MLP via FCM-MCA classifier structure has the highest ratio of classification accuracy and has the best performance superior to other methods; and that Smoking was the most factor causing heart disease. Originality/value This paper shows the importance of integrating statistical methods in increasing the classification accuracy of heart disease data.
Keywords: 330; Fuzzy c-means; Heart disease; Multilayer perceptron; Multiple correspondence analysis; Principal component analysis; Radial basis function networks